A OCUPAÇÃO RACIONAL DA ARTE NA EDUCAÇÃO FORMAL: UM ESTUDO DESDE A PERSPECTIVA DA CRIATIVIDADE - Rosa, Maisi Matilde Garcia Sathler (2011)
Arts and creativity are essential elements for individual, social, cultural growth as well as for the development of society. However, since the sixteenth century we live strongly influenced by the parameters of cognitive instrumental rationality. particularly in western culture has been dominates the overvaluation of objectivity, rationality and the hard sciences to the detriment of artistic creation. This research examines the rational of art and its influence on limiting the creativity in the school environment. Thus, analyzing the different conceptions of creativity, in the light of historical evolution and the influences of inherited socio-cultural context. Also considers the concept of art/ education in its relation to the historical conditions of insertion of formal education in Brazil. Finally, this paper identifies the hallmarks of rationality in current educational processes in Brazil, with reference to contemporary theories. The conclusion of this study may serve as a basis for providing subsidies to reflect on the need for renewal of views on creativity as an instrument of intellectual education, the teaching of arts in the school context.